Increased Captagon tablets seizures in Saudi Arabia - Alahmadi, Tareq (Technium: Romanian Journal of Applied Sciences and Technology, 2020)
Captagon tablets are an addictive amphetamine stimulant that can cause anxiety, high blood pressure, and rapid heart rate. For these reasons, it was banned in 1986. However, there have been an increasing number of attempts to smuggle these drugs into Saudi Arabia in large quantities.Thus, the smuggling of Captagon tablets has become a significant source of income among the youth, and Captagon consumption has increased in the Kingdom of Saudi Arabia. This article focuses on the issue of Captagon smuggling to Saudi Arabia, which increased between 2009 and 2015, according to recent statistics. Method: Seven years of data (2009–2015) related to the smuggling of Captagon tablets into Saudi Arabia were analyzed. The data were obtained by Saudi Customs and other governmental entities responsible for monitoring the smuggling of drugs. Results: The smuggling of Captagon tablets has increased in Saudi Arabia since 2009. Indeed, among all other drugs that have been smuggled into Saudi Arabia since 1999, Captagon tablets are the most smuggled narcotic. Conclusion: Statistically, the number of Captagon tablets seized in drug cases has grown annually. Moreover, Alhadetha Port is the most vulnerable to the smuggling of Captagon tablets. As such, intervention programs are needed to address the problem of Captagon tablets’ smuggling. In addition, awareness among the youth needs to be increased through cooperation between public education and higher education.